The Impact of Employee Creativity On Innovative Work Behaviour - Noor Hakim, Puteri Nur Malyana; Wahab, Eta (Research in Management of Technology and Business, 2023)
Employee creativity is the potential to create ideas that leads to innovation. This study will be conducted because less studies on innovation in hotel industry had been conducted in Malaysia. Hence, innovative work behaviour is a complicated behaviour of employees that generate, promote and implement ideas. This study tries to determine the association between creativity of the employee and their innovative work behaviour. The objectives of this research is to identify the level of employee creativity in the hotel industry in Johor Bahru, the level of innovative work behaviour among employees in hotel industry in Johor Bahru and to identify the relationship between employee creativity and innovative work behaviour in hotel industry in Johor Bahru. Quantitative data have been utilised in this study. An online survey had been conducted among 302 employees in hotel industry in Johor Bahru, Johor with a response rate of 51.32%. Data had been analysed using both descriptive and Spearman’s correlation analysis. This study found that the level of employee creativity and innovative work behaviour were high. This study also shows a significant relationship between employee creativity and innovative work behaviour